2023
DOI: 10.1002/ijc.34574
|View full text |Cite
|
Sign up to set email alerts
|

Risk of epithelial ovarian tumors among women with polycystic ovary syndrome: A nationwide population‐based cohort study

Abstract: An association between polycystic ovary syndrome (PCOS) and epithelial ovarian tumors is biologically plausible as conditions inherent to PCOS such as excessive androgenic hormones, reproductive factors and obesity are also risk factors for these hormone-sensitive tumors. However, previous studies have showed conflicting results and have various methodological limitations. This population-based cohort study investigates the association between PCOS and epithelial ovarian tumors and includes all women born in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A linkage study identified FST as a candidate gene for polycystic ovary syndrome (PCOS) 78 . PCOS may be associated with an increased risk of borderline or postmenopausal ovarian cancer 79 , although a recent Mendelian Randomization study found that genetically predicted PCOS was associated with decreased risk of ovarian cancer 80 . A GWAS of African ancestry women found rs37792 near FST to be genome-wide statistically significantly associated with HGSOC in African ancestry women 81 .…”
Section: Discussionmentioning
confidence: 99%
“…A linkage study identified FST as a candidate gene for polycystic ovary syndrome (PCOS) 78 . PCOS may be associated with an increased risk of borderline or postmenopausal ovarian cancer 79 , although a recent Mendelian Randomization study found that genetically predicted PCOS was associated with decreased risk of ovarian cancer 80 . A GWAS of African ancestry women found rs37792 near FST to be genome-wide statistically significantly associated with HGSOC in African ancestry women 81 .…”
Section: Discussionmentioning
confidence: 99%